Antioxidant and Textural Properties and Aroma and Fatty Acid Profile of Meatless Cig Kofte, a Special Food in Turkey, Produced by Industrial Processing - Ozturk, I.; Karaman, S.; Tastemur, B.; Tornuk, F.; Sagdic, O.; Kayacıer, Ahmed (Blackwell Publishing Ltd, 2016)
In this study, 10 cig kofte samples collected from different producers were analyzed. Dry matter, pH and water activity values were in the range of 34.13-53.40%, 4.67-5.03 and 0.934-0.967, respectively. Major fatty acids were determined to be oleic and linoleic acid, and the samples showed similar fatty acid profiles. Linoleic acid was the most abundant fatty acid and its level was in the range of 0.94-54.13% in the samples. Textural parameter magnitudes of the samples, except for one, were determined to be close to each other. A total of 44 volatile compounds were determined in the samples and the major ones were limonene and gamma terpinene. Total phenolic contents of the samples were determined to be in the range of 56-132.1mg gallic acid equivalent/g dry extract. In conclusion, variable properties were observed in the retailed meatless cig kofte samples sold in Turkey. © 2016 Wiley Periodicals, Inc.
Keywords: [No Kerywords]